1999
DOI: 10.1046/j.1365-2958.1999.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the gene (cpe ) encoding Clostridium perfringens enterotoxin eliminates the ability of two cpe‐positive C. perfringens type A human gastrointestinal disease isolates to affect rabbit ileal loops

Abstract: SummaryPrevious epidemiological studies have implicated Clostridium perfringens enterotoxin (CPE) as a virulence factor in the pathogenesis of several gastrointestinal (GI) illnesses caused by C. perfringens type A isolates, including C. perfringens type A food poisoning and non-food-borne GI illnesses, such as antibiotic-associated diarrhoea and sporadic diarrhoea. To further evaluate the importance of CPE in the pathogenesis of these GI diseases, allelic exchange was used to construct cpe knock-out mutants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
174
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 25 publications
2
174
0
1
Order By: Relevance
“…C. perfringens type A strains produce the chromosomal-encoded alpha-toxin, while C. perfringens type C strains produce alpha toxin together with beta toxin (Petit et al, 1999). Some strains of C. perfringens type A produce an enterotoxin at the moment of sporulation, causing disease in humans (Ridell et al, 1998;Sarker et al, 1999). The mechanism of action of the enterotoxin will be discussed further in the text.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…C. perfringens type A strains produce the chromosomal-encoded alpha-toxin, while C. perfringens type C strains produce alpha toxin together with beta toxin (Petit et al, 1999). Some strains of C. perfringens type A produce an enterotoxin at the moment of sporulation, causing disease in humans (Ridell et al, 1998;Sarker et al, 1999). The mechanism of action of the enterotoxin will be discussed further in the text.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…CPE is both necessary and sufficient for obtaining the gastrointestinal (GI) symptoms of C. perfringens type A food poisoning (Sarker et al , 1999;, the third most frequently identified foodborne illness in the USA (Bean et al ., 1996). This enterotoxin also contributes (Sarker et al ., 1999) to the GI symptoms of up to 5-20% of all cases of non-foodborne human GI diseases (Carman, 1997) and may be involved in certain veterinary diarrhoeas (Songer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This toxin is both necessary and sufficient for the enteric virulence of C. perfringens type A food poisoning isolates. Specific inactivation of the enterotoxin gene (cpe) by allelic exchange was shown to render a C. perfringens food poisoning isolate avirulent in rabbit ileal loops, and intestinal virulence could be restored by complementing that mutant with a cloned copy of the wild-type cpe gene (16). Furthermore, ingestion of purified CPE by human volunteers was determined to be sufficient for reproducing the cramping and diarrheic symptoms of the natural food poisoning (18).…”
mentioning
confidence: 99%